Solusi Sehat dan Ekonomis Melalui Budidaya Tanaman Obat Keluarga Desa Karang Panggung - Sekar Ayu Ningsih; M. Ergiyandi Barokha; Richwan Gunawan Simbolon; Nadya E E Nainggolan; Fransiska Aprilia Ayu P; Barika Barika (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
Community service activities regarding the utilization of Family Medicinal Plants (TOGA) are designed to increase the awareness of village officials regarding the benefits of TOGA, provide training related to cultivation, minimize dependence on chemical drugs, and make Karang Panggung village officials. This program aims to promote the use of TOGA as an affordable and independent alternative health solution. The program was implemented by Group 9 of the Bengkulu University Development Economics Department in Karang Panggung Village, Merigi Sakti District, Central Bengkulu Regency. This village has an area of 3 km² with undulating geographical conditions. The program began with a survey to determine suitable land and types of medicinal plants that could be planted in the village. The main activity, namely the survey, was carried out on November 7, 2024 and planting as well as socialization on November 19, 2024, the planting location on the land that had been prepared at the Karang Panggung Village office. Planting was carried out together with village officials, with the aim of building a Living Pharmacy Garden that is easy to maintain and monitor. This activity shows the enthusiasm of village officials who actively support the program, as well as the availability of TOGA planting facilities that are expected to be utilized by the community in a sustainable manner. This program contributes to increasing community awareness of the importance of TOGA and becomes an example for other villages in managing family medicinal plants.